Karta I︠U︡gorskago Shara po robotamʺ Gidrograficheskoĭ Ėkspedit︠s︡īi Si︠e︡vernago Ledovitago okeanʺ proizvedennym podʺ nachalʹstvomʺ Polkovnika Vilʹkit︠s︡kago vʺ 1898, 1899 i 1900 g. g. / Kopriroval khimicheskoi︠u︡ K. Fedorovʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; [Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе, 1901)
Relief shown by hachures. Depths shown by soundings and isolines.; Title translation: Map of Yugor Strait according Hydrographic Expedition of the Arctic Ocean produced under the direction Colonel Vilkitsky in 1898, 1899 and 1900.; Yugor Strait is also known as Yugorski shar, Yugorsky shar, Yugorski shar or Yugorskiy shar.; Coordinates given for Yugor Strait given on map: 69°39'19.0"N 60°25'37.5"E.; Greenwich meridian.; "No. 576" -- bottom right margin Grayscale; 1:60,000